Show-ha Shoten! Volume 4 - Asakura, Akinari, 1989- (Shonen Jump manga., 2024)
Shy Azemichi Shijima has secretly been studying the art of comedy. His outgoing classmate Taiyo Higashikata has big dreams of being funny but no follow-through. When the two team up, they just might take the comedy world by storm! Azemichi and Taiyo are One-Way Ticket to the Top, the final performers of the Wara-1 Koshien prelims! Between Azemichi's carefully scripted comedy and Taiyo's flawless acting, they've got the perfect routine to win over the crowd. But despite starting off with the biggest laughs of the day, Azemichi draws a blank halfway through their routine and forgets his next line! Unless Azemichi and Taiyo can save their performance, they may have just lost their only chance at making their comedy dreams come true...